2006
DOI: 10.1128/jvi.80.3.1077-1086.2006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an NF-κB-Dependent Gene Network in Cells Infected by Mammalian Reovirus

Abstract: Reovirus infection activates NF-B, which leads to programmed cell death in cultured cells and in the murine central nervous system. However, little is known about how NF-B elicits this cellular response. To identify host genes activated by NF-B following reovirus infection, we used HeLa cells engineered to express a degradation-resistant mutant of IB␣ (mIB␣) under the control of an inducible promoter. Induction of mIB␣ inhibited the activation of NF-B and blocked the expression of NF-B-responsive genes. RNA ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
39
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 63 publications
6
39
0
Order By: Relevance
“…Significant functional compensation between members of the NF-B/Rel family has previously been shown for a small group of genes in response to TNF-␣ in fibroblasts lacking various NF-B family members (34). In addition, there is significant overlap both in the functional groupings and in the specific genes affected by c-Rel deletion and those affected in other expression profiling studies where NF-B activation was globally inhibited (35)(36)(37). Small scale studies of genes affected by RelA deletion in RelA Ϫ/Ϫ mouse embryonic fibroblasts (34) or RelA RNA interference treatment in HeLa cells (38) also identified genes such as IP-10, Bcl2l1, and IB␣ as RelA targets, suggesting a common gene expression program executed by the NF-B/Rel family of transcription factors.…”
Section: Discussionmentioning
confidence: 68%
“…Significant functional compensation between members of the NF-B/Rel family has previously been shown for a small group of genes in response to TNF-␣ in fibroblasts lacking various NF-B family members (34). In addition, there is significant overlap both in the functional groupings and in the specific genes affected by c-Rel deletion and those affected in other expression profiling studies where NF-B activation was globally inhibited (35)(36)(37). Small scale studies of genes affected by RelA deletion in RelA Ϫ/Ϫ mouse embryonic fibroblasts (34) or RelA RNA interference treatment in HeLa cells (38) also identified genes such as IP-10, Bcl2l1, and IB␣ as RelA targets, suggesting a common gene expression program executed by the NF-B/Rel family of transcription factors.…”
Section: Discussionmentioning
confidence: 68%
“…Efficient apoptosis induction following reovirus infection is dependent on the transcription factors IRF-3 and NF-B (20,34,35). Despite this association, microarray analysis of NF-Bdependent genes induced following reovirus infection did not identify a readily apparent mechanism for the initiation of apoptosis (58). However, a number of transcriptional networks that couple to apoptotic signaling pathways were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Microarray studies of gene expression following reovirus infection revealed that several ISGs are rapidly upregulated following infection in an NF-B-dependent manner (58). However, those studies did not identify a mediator of proapoptotic signaling that could readily explain the cell death pathways initiated by reovirus infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High-density microarray analyses of cells expressing a regulated dominant-negative NF-B inhibitor have elucidated the genes under control of the canonical NF-B activation pathway in epithelial cells subjected to viral infections (40,55) and cytokine stimulation (56) and those controlled by its distinct activation modes (54). These studies have shown that in response to TNF stimulation, NF-B binding controls the expression of a noncontiguous group of genes whose products control a variety of biological processes, including leukocyte activation/chemotaxis, negative regulators of the TNF-IKK pathway, cellular metabolism, antigen processing, and others (54).…”
mentioning
confidence: 99%